2009
DOI: 10.1089/apc.2008.0132
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Implications of Timely Linkage and Early Retention in HIV Care

Abstract: Following HIV diagnosis, linkage to outpatient treatment, antiretroviral initiation, and longitudinal retention in care represent the foundation for successful treatment. While prior studies have evaluated these processes in isolation, a systematic evaluation of successive steps in the same cohort of patients has not yet been performed. To ensure optimal long-term outcomes, a better understanding of the interplay of these processes is needed. Therefore, a retrospective cohort study of patients initiating outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
271
6
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(299 citation statements)
references
References 39 publications
16
271
6
6
Order By: Relevance
“…54 For HIV-infected patients in particular, improved access has been associated with better engagement in care and health-related quality of life, 55,56 more cost-effective health services utilization, 57 and timelier initiation of antiretroviral therapy. 58 Collaborative care also offers the potential to "up-skill" non-HIV-expert providers through individual, patient-based education: for example, providers may learn how to better address antiretroviral adherence, recognize HIV treatment failure, and manage serious infection-and therapy-related complications. Finally, community-based care may be appealing to patients who prefer not to access HIV-identified facilities due to fears regarding stigma.…”
Section: Models For Hiv Carementioning
confidence: 99%
“…54 For HIV-infected patients in particular, improved access has been associated with better engagement in care and health-related quality of life, 55,56 more cost-effective health services utilization, 57 and timelier initiation of antiretroviral therapy. 58 Collaborative care also offers the potential to "up-skill" non-HIV-expert providers through individual, patient-based education: for example, providers may learn how to better address antiretroviral adherence, recognize HIV treatment failure, and manage serious infection-and therapy-related complications. Finally, community-based care may be appealing to patients who prefer not to access HIV-identified facilities due to fears regarding stigma.…”
Section: Models For Hiv Carementioning
confidence: 99%
“…Delayed linkage and poor retention in outpatient HIV care have been associated with delayed receipt of antiretroviral medications, higher rates of viral load failure, and increased morbidity and mortality. [5][6][7][8][9][10][11][12][13][14][15][16][17] Beyond the effects on individual health, engagement in HIV care has important consequences for the public health as it plays a pivotal role in HIV transmission and secondary HIV infections. Studies have demonstrated reduced risk transmission behavior among HIVinfected patients engaged in clinical care, 18,19 and viral load suppression, which is achieved more commonly among those with better retention, 6,9 also reduces risk of transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, the majority of which have been retrospective and observational in design, have used a number of differing approaches to measure retention in care. [5][6][7][8][9][10][11][12][13][14][15][16][17] To date, there has not been a published summary of these measures to serve as a guide and provide a common nomenclature for HIV retention measures. A recent review of retention in care noted, ''a clear framework for how patient retention is defined and how it should be measured remains outstanding.''…”
Section: Introductionmentioning
confidence: 99%
“…age, sex or gender, income, immigration status) [6][7][8][9][10][11][12], psychosocial factors (e.g. mental health status, substance use, homelessness) [13][14][15], and geographic factors (e.g.…”
Section: Introductionmentioning
confidence: 99%